Elevated salivary IgA, decreased anxiety, and an altered oral microbiota are associated with active participation on an undergraduate athletic team - Lamb, A. L.; Hess, D. E.; Edenborn, S.; Ubinger, E.; Carrillo, A. E.; Appasamy, P. M. (Physiology & Behavior, 2017)
Background: Previous reports indicate that regular, but not excessive, exercise can moderate the response to anxiety and alter the immune response, therefore we hypothesized that college student athletes who were actively participating on an NCAA Division III athletics team ("in-season") would have lower levels of anxiety and higher salivary IgA levels than similar college athletes who were in their "off-season". NCAA Division III athletes participate in athletics at a level of intensity that is more moderate compared to other NCAA divisions. Alterations in the microbiome have been associated with alterations in psychosocial well-being and with exercise. Therefore, we also proposed that the oral microbiota would be different in "in-season" versus "off-season" athletes.